ANALISIS HUKUM TINDAK PIDANA PEGAWAI NEGERI SIPIL SEBAGAI PELAKU PIDANA KORUPSI PENGADAAN BARANG (STUDI PUTUSAN NO.114/PID.SUS-TPK/2018/PN.MDN) - MONALISA SIAHAAN (JURNAL ILMIAH MAKSITEK, 2021)
Criminal acts are a term that is officially used in indonesian laws and regulations. In the writings of Indonesian criminal lawexperts, sometimes the term "delict" is sometimes used as the equivalent of the term "Criminal Act".The term "Delik" comesfrom the word "delict" in Dutch. There are also those who use the term "Criminal Acts" for criminal acts. The criminal code(Criminal Code) which is based on the Dutch penal code (Wetbook Van Strafrecht) then the original term is the same,namely Strafbaar feit (Acts prohibited by the Law and threatened with Punishment). Corruption is generally defined as an actrelated to the public interest or the wider community for personal interests and or certain groups that basically hint at a badmeaning and harm the state and society. According to the Legal Dictionary, Corruption is the misappropriation orembezzlement of State or Corporate money as a place where a person works for personal or other interests. Civil Servants(PNS) are people who work in the government or state. Article 1 of Law No. 43 of 1999 provides the understanding of civilservants are those who after fulfilling the conditions specified in the regulations in applicable laws and regulations, appointedby authorized officials and assigned duties in a State office or handed over to other State duties stipulated based on a lawand paid according to applicable laws and regulations.